Field Guide to Identify the Common Casuarina (Australian Pine) Species in Florida - William S. Castle (EDIS, 2008)
HS-1140, an 8-page illustrated field guide by William S. Castle, provides practical information and photographs for anyone interested in field identification of these plants. Published by the UF Department of Horticultural Sciences May 2008.